Optimization of Regional Development Planning Through the Integration of SIPD Data in Tebing Tinggi City - Panjaitan, Lasmian; Harianja, Yohana Ewicha; Siregar, Hairani; Sembiring, Mutia; Irawan (CV Raskha Media Group, 2025)
Effective and efficient regional development planning is key to achieving sustainable development goals. In Tebing Tinggi City, the implementation of the Regional Government Information System (SIPD) is the main framework in the management of development data. However, the main challenge faced is the lack of optimal data integration between SIPD modules, which impacts data incompatibility, data duplication, and inaccurate planning decisions. This study aims to analyze and formulate a model for optimizing regional development planning through the integration of SIPD data in Tebing Tinggi City. The research method used is qualitative descriptive with data collection through journals/articles. The results of the study show that data integration is not optimal due to technical factors, lack of coordination between OPDs, and limited operator competencies. The proposed optimization model emphasizes three main pillars, namely Data Governance Alignment through the formation of an integrated data coordination team and the establishment of Standard Operating Procedures (SOPs) for data integration across OPDs, Data Quality Improvement and Standardization by implementing single metadata and validating periodic data, and Strengthening HR Capacity through technical and functional training. Optimal data integration is expected to produce more consistent, accurate, and evidence-based planning documents (RKPD and Renja), thereby supporting better decision-making and more targeted budget allocation in Tebing Tinggi City.